Continuidade do cuidado da criança na atenção primária à saúde em região de fronteira - Picco, Taigra Morgana (2019)
Introduction: The continued care of the child in the first years of life is essential to monitor their growth and development and to identify possible changes that require investigation or interventions. The relevance of monitoring children through childcare in primary health care for positive outcomes in maternal and child morbidity and mortality indicators conditioned the implementation of Rede Mãe Paranaense, in the State of Paraná, in 2012. The adequate continuity of child care, after birth, is an essential factor for timely interventions on potential risk factors for the child's health. Objective: to understand the continuity of child care in primary health care in a border region. Method: This is a qualitative study, carried out in primary health care, in the city of Foz do IguaçuPR, Brazil. 14 mothers of children aged zero to 24 months, who performed childcare in basic health units or family health strategy participated, and five nurses from these units. Data collection was carried out through semi-structured interviews, from March 2018 to June 2019. Thematic content analysis guided the data analysis. Results: The results are presented in the form of two manuscripts. The first, entitled Continuity of child care in primary health care in a border region, shows the importance of childcare consultation and immunization for the continuity of child care after hospital discharge; reveals the challenges and obstacles to breastfeeding in the experience of mothers and points to the heel test as a fragile component of neonatal screening. The second manuscript, entitled Common ildhood diseases and the continuity of care for infants in a border region, presents common childhood diseases, which condition demand for primary health care and or lead to the use of popular practices by mothers, for circumvent them; shows weaknesses in the actions and services of primary health care, particularly regarding home visits, active search for mothers who are absent from childcare, provision of medicines, which are related to the lack of professionals and materials. Conclusion: It is concluded that childcare consultations and immunization are the main components of primary health care for the continuity of child care. It points to the need for actions by managers and health professionals to promote exclusive breastfeeding until the child's six months of life, to prevent errors in the procedure for collecting the baby's foot test, to offer human and material resources for meet the demands of primary health care, enabling adequate planning and implementation of actions for the continuity of child care in this area. With regard to the border region, children born in Brazilian territory, daughters of Paraguayan or Brasiguaian mothers, although they are entitled to care by the Brazilian health system, do not perform childcare routinely. Therefore, agreements are required between health managers in countries bordering on countries to ensure continuity of care for Brazilian children.